The interplay of digital fatigue and sleep deprivation in adolescent mental health: a post-pandemic imperative for school nursing - Hoshiar Singh; Ayushi Rana; Kanchan Sharma (International Journal Of Community Medicine And Public Health, 2026)
The risk of high pre-sleep screen use, delayed sleep onset time, and increased insomnia among adolescents has increased significantly following and during the COVID-19 pandemic, which has also significantly increased their digital technology use. Sleep loss also exacerbates mental health concerns including depression, anxiety, emotional dys-regulation and suicidality, disproportionately affecting female adolescents, youth with attention-deficit/hyperactivity disorder (ADHD) and/or autism spectrum disorders, and socioeconomically disadvantaged groups. This is a narrative review of peer-reviewed literature (2020-2024) that reviews the relationships among digital fatigue, sleep deprivation and adolescent mental health, and the role of school nurses in multi-tiered systems of support (MTSS) to address the interlinked risks. Peer-reviewed articles, systematic reviews, and meta-analyses were identified through PubMed, Scopus, and Google Scholar using a combination of the following terms: adolescents, digital fatigue, sleep deprivation, screen time, mental health, school nursing, and COVID-19. Studies were included if they included adolescents aged 10–19 years, and addressed digital screen use and sleep or psychological outcomes, and were published in or after 2020. Evidence was integrated within and across domains. Screen time, especially in the hours leading up to sleep, was consistently linked to a reduced sleep onset, poor sleep quality, and an increase in insomnia, through the suppression of melatonin and stimulation of cognitive activity. Disruption of sleep was associated with depression, anxiety, and suicidality, with a bidirectional relationship exacerbated by pandemic-related stress and less physical activity. School nurses became the front-line MTSS moderators in screening, education and policy advocacy. Culturally responsive, longitudinal studies, and more robust implementation of school nursing programs are needed to safeguard adolescent mental health and combat adolescent digital fatigue and sleep loss.